Recent Approaches to Modify Poly(vinyl chloride) Chemical Structure - Hasan, Amer A.; H. Al-Mashhadani, Mohammed; Al-Dahhan, Wedad H.; Yusop, Rahimi M.; Yousif, Emad A. (Al-Nahrain Journal of Science, 2022)
Since its first discovery in the nineteenth century, polymer researchers have continued to study poly(vinyl chloride). Its characteristics, such as its thermal instability, are delicate by its structural flaws that result from its containing chlorine atom which is sensitive to UV light as a good leaving group. Many researchers suggested adding various types of organic and inorganic additives as photo and/or thermal stabilizers of poly(vinyl chloride). Recently this work has been expanded by extensive ongoing research to modify the chemical structure of poly(vinyl chloride) by replacing part of the chlorine atoms with other molecules which could enhance its stability against weathering circumstances. The last was carried out not only for common chemical reactions but also to improve the characteristics of poly(vinyl chloride) in particular applications. Based on reports from the past ten years, this study outlines many of the chemical alterations of poly(vinyl chloride) as well as associated uses. These alterations are organized following the modification of poly(vinyl chloride) through Carbon-Carbon and Carbon-Nitrogen linkages.